Bringing Semantics to Web Services: Model driven approach - Bensaber, Djamel Amar; Benslimane, Djamal; Malki, Mimoun; Benslimane, Sidi Mohamed (INFOCOMP Journal of Computer Science, 2008)
The semantic web promises automates invocation, discovery and composition of web services by enhancing services with semantic descriptions. This paper describes a model driven approach to facilitate the construction of OWL-S specifications. The methodology is divided into three main steps. In the first step we reverse engineered WSDL documents into UML profile models that enable the use of high-level graphical models as an integration platform for semantic web services. In the second step, suitable domain ontologies are used for the semantic annotation of the UML models. Finally, in the third step a conversion tool will generate automatically the OWL-S description from these UML models. The UML profile provides flexibility as it can expresses multiple semantic web service concepts.